Ibn Nujaym’s Thoughts on Legal Maxims (Qawâ`id al-Fiqhiyyah): An Analysis of Their Application to Juridical Issues - Jalili, Ismail (Madania: Jurnal Kajian Keislaman, 2023)
Legal maxims possess a unique place in jurisprudence, and jurists of all schools recognize it as a basis for forming sharia opinions, particularly if they are based on the holy Quran and prophetic traditions. Ibn Nujaym al-Hanafi was a prominent jurist from the Hanafi school who paid special attention to legal maxims (qawâ`id  al-fiqhiyyah) and compiled them in his books al-Ashbah wa al-Nazhâ’ir and al-Fawâ’id al-Zainiyyah, etc. He also wrote commentaries on various subjects in his other books. He became one of the most distinguished jurists in this discipline and the Hanafi school. The purpose of this article was to examine the accuracy of Ibn Nujaym's perspectives on the Islamic legal maxim, the explanation of the most significant five maxims, and how they can be applied to some juridical issues. This study employed a qualitative method and a content analysis approach. The data was obtained through a search of books, journals, and other sources of information. The collected data were analyzed qualitatively and deliberated. The findings of study show that Ibn Nujaym al-Hanafi's masterpiece al-Ashbah wa al-Nazhâ’ir became the leading work on legal maxims and was acknowledged as authoritative by Hanafi jurists. Qawâ`id al-fiqhiyyah memiliki kedudukan yang istimewa dalam eksistensi hukum Islam, dan para ulama dari berbagai mazhab fikih pun mengakui keistimewaan tersebut, sebab ia dapat digunakan untuk menghasilkan fatwa (pandangan hukum syariah), terutama jika ia dibentuk berdasarkan Alquran dan Hadis. Ibn Nujaym al-Hanafi adalah seorang ahli hukum terkemuka dari kalangan mazhab Hanafi yang telah mencurahkan perhatian dan pemikirannya terhadap eksistensi qawâ`id  al-fiqhiyyah. Pemikiran beliau tentang tema ini tertuang dalam buku beliau yang berjudul al-Ashbah wa al-Nazhâ’ir, al-Fawa’id al-Zainiyyah, dan lain-lain. Bahkan, buku al-Ashbah wa al-Nazhâ’ir, menjadi salah satu rujukan terkemuka dalam kajian tema qawâ`id al-fiqhiyyah, mewakili pandangan ulama mazhab Hanafi. Tujuan artikel ini adalah untuk mengkaji pemikiran Ibnu Nujaym tentang qawâ`id al-fiqhiyyah, dan penjelasan tentang lima macam qawa’id al-fiqhiyyah yang utama, serta bagaimana qawâ`id al-fiqhiyyah dapat digunakan untuk menjawab beberapa permasalahan fikih. Penelitian ini menggunakan metode kualitatif dengan pendekatan analisis konten. Data diperoleh melalui pencarian buku, jurnal, dan sumber informasi lainnya. Data yang terkumpul dianalisis secara kualitatif dan ditampilkan secara menyeluruh. Penelitian ini mendapatkan bahwa karya agung Ibnu Nujaym, yaitu al-Ashbah wa al-Nazhâ’ir, menjadi karya terkemuka yang membahas tentang qawâ`id al-fiqhiyyah dan telah diakui sebagai pandangan ilmiah yang terpercaya dalam mazhab Hanafi. Dan qawâ`id al-fiqhiyyah dapat digunakan untuk menjawab beberapa permasalahan fikih (qadhiyah fiqih).